Sociodemographic factors affecting knowledge levels of tuberculosis patients in New Delhi - Ilham Zaidi; P. S. Sarma; Khalid Umer Khayyam; Quazi Toufique Ahmad; V. Ramankutty; Gurpreet Singh (Journal of Family Medicine and Primary Care, 2024)
Background: Sociodemographic factors can significantly influence the knowledge level of tuberculosis (TB) patients, affecting the overall health outcomes. Due to lack of awareness and the stigma associated with TB, Indian TB elimination efforts are facing challenges. Patients with less information are more likely to experience delays in diagnosis and proper care. Method: A cross-sectional study was conducted in New Delhi across 26 operational National TB Elimination Program districts, involving 200 adult pulmonary TB patients receiving treatment from April to August 2020. A structured questionnaire guided the interviews, followed with bivariate analysis and descriptive statistics used for analysis. Results: Predominantly, residents of semiurban regions accounted for the highest proportion (70.5%), followed by urban areas (20.5%), with rural areas/slums comprising a minority (9%). Notably, a significant majority (94.5%) reported residing in individually owned dwellings, with shared accommodations limited to a minority (5.5%). Sanitary facilities varied, with 77% possessing personal toilets, 18.5% utilizing private facilities, and only 4.5% relying on public toilets. Awareness levels about TB reflected moderate awareness among 56% of participants, good knowledge among 41%, and minimal awareness (poor knowledge) among only 3% of respondents. Conclusion: Age, sex, socioeconomic level, kind of lodgings, malnutrition, and personal cleanliness should all be taken into account for TB treatment adherence. A new set of frameworks should be developed to enhance the living circumstances of high-risk populations and patients who are living in crowded locations since sharing a room or a house in a populated region increases the risk of TB transmission.